Minor regression and long-time survival (56 months) in a patient with malignant pleural mesothelioma under Viscum album and Helleborus niger extracts—a case report - Werthmann, Paul G.; Saltzwedel, Gerhard; Kienle, Gunver S. (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Malignant pleural mesothelioma (MPM) is a rare cancer with a dismal prognosis. Viscum album extracts (VAE) have strong immune stimulatory properties, cytotoxic effects, can downregulate cancer genes and inhibit angiogenesis. VAE are often used as an adjunct treatment in cancer patients but have rarely been investigated in MPM. Helleborus niger extracts (HNE) have been used in anticancer therapy since antiquity, and also show tumor specific cytotoxic effects. We present a case of a 64-year old woman with epithelioid MPM of the right chest with node involvement (T2N1M0, stage III). Deciding against the recommended radio-chemotherapy, surgery and pleurodesis, she opted for an integrative treatment approach and was treated with VAE and HNE. After 6 weeks’ treatment, the pleural and nodal MPM manifestations were reduced by about 15%. Subsequent tumor growth was slow, and the patient remained in good health, enabling her to remain physically active until shortly before her death 56 months after the initial diagnosis. This is a rare case of an MPM patient not receiving any standard anticancer treatment; it still shows an extraordinary long survival and good performance status. We presume that VAE and HNE might had an impact on this clinically relevant outcome and therefore should be further investigated in MPM.